Aspek Yuridis Eksplorasi Sektor Minyak dan Gas Dengan Menggunakan Norway Model - Muhamad Azhar (Magister Kenotariatan Universitas Diponegoro, 2021)
AbstractTo achieve good and profitable governance management, synergy is needed between the government both in terms of supervision and regulation with the exploration company, because if this synergy does not exist then this management itself will be difficult. The purpose of this study is used to determine the extent of the concept. The Norway model or “triangle A” is the most suitable thing for this country. This study uses a comparative method to show advantages over other methods accompanied by juridical aspects to strengthen the legal basis. The country of Indonesia can take the